Essays on corporate governance in Chinese listed firms : a thesis presented in fulfilment of the requirement for the degree of Doctor of Philosophy in Finance at Massey University, Manawatu campus, New Zealand - Wang, Lu (Massey University, 2022)
This thesis consists of three essays. In the first essay, we investigate government resource allocation through related-party transactions (RPTs) using hand-collected data of RPTs between non-corporate government agencies and state-owned enterprises (SOEs) in China. It shows that more resources are allocated to SOEs with a politically connected chairman of the board, small SOEs and SOEs located in less-developed regions. The results indicate that Chinese governments allocate more resources through RPTs to SOEs with stronger political incentives and promote the new wave of Chinese SOE reform. However, in SOEs with a politically connected chairman, resources obtained through RPTs are only associated with increased investment expenditure and not with SOEs’ labour intensity. This essay explores a unique channel of government resource allocation among SOEs and provides evidence to the critical view of government intervention. The second essay investigates the effects of top executives’ reputation concern on earnings quality in China’s listed SOEs. Existing studies on executive reputation mainly focus on executives in a competitive executive labour market. Therefore, it is of great interest to examine whether reputation concern matters to top executives in SOEs, whose career development heavily depends on the preference of government bureaucrats. We define chairpersons with concurrent positions in listed SOEs’ shareholding firms as “spotlight” executives that may receive more external attention. The evidence shows that “spotlight” executives positively influence the earnings quality of SOEs measured by earnings management via RPTs. Such a positive influence is achieved through the intensive external attention paid to those executives in the spotlight. However, the positive reputation effect becomes insignificant when the political objectives of SOEs are pronounced. Further evidence shows that the positive impact of “spotlight” executives on earnings quality is shaped by various characteristics of SOEs, such as different types of state control, the industry sectors SOEs come from, firm performance, the timing of seasoned equity offerings external monitoring. Essay three studies whether and if so, how managerial efficiency influences stock price crash risk in China’s listed firms. The evidence suggests that executives with better efficiency can reduce stock price crash risk, and the beneficial effect is achieved through improved firm information transparency and lower excessive risk-taking. Further, the beneficial impact of managerial efficiency on crash risk is more pronounced in SOEs, firms located in less developed regions and firms that pay higher compensation to managers. This essay sheds light on the influence of managerial ability in emerging markets with weak institutions, such as China. Evidence from the three essays is robust after considering endogeneity issues. The three essays provide important policy implications. First, imposing government intervention on SOEs does not lead to efficient usage of government resources. Second, the spotlight is a powerful mechanism to discipline managerial behaviour in SOEs. In addition, free SOEs from political interference tends to facilitate the monitoring of the spotlight. Third, it is essential for firms in emerging markets, especially SOEs, to adopt methods of evaluating managerial efficiency and select managers that provide better efficiency, as they can not only utilize company resources and produce outputs more efficiently, but also improve firm transparency, reduce excessive risk-taking, and thus reduce stock price crash risk.
Keywords: Corporate governance; China; Government business enterprises; Management; Executives; 350701 Corporate governance